2014
DOI: 10.1002/chem.201304824
|View full text |Cite
|
Sign up to set email alerts
|

Structural Effects in Lithiocuprate Chemistry: The Elucidation of Reactive Pentametallic Complexes

Abstract: TMPLi (TMP=2,2,6,6-tetramethylpiperidide) reacts with CuI salts in the presence of Et2O to give the dimers [{(TMP)2Cu(X)Li2(OEt2)}2] (X=CN, halide). In contrast, the use of DMPLi (DMP=cis-2,6-dimethylpiperidide) gives an unprecedented structural motif; [{(DMP)2CuLi(OEt2)}2LiX] (X=halide). This formulation suggests a hitherto unexplored route to the in situ formation of Gilman-type bases that are of proven reactivity in directed ortho cupration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…The isolation and characterization of lithium cyanocuprates 1a–c , which were prepared using amidolithium reagents with CuCN, revealed the bonding characteristics of Cu in systems that could demonstrate either higher or lower order structural properties. In line with theoretical expectations, 14 lower order (TMP) 2 Cu(CN)Li 2 (L) (L = OEt 2 , THF, THP = tetrahydropyran) 17 , 18 structures were observed crystallographically, with agglomeration giving essentially planar dimers based on lithium–nitrogen cores ( Scheme 1 ). The observation that, whilst in other respects 1a–c pertained to Lipshutz cuprate characteristics, they lack a Cu–CN interaction led to investigation of the generality of this motif.…”
Section: Introductionsupporting
confidence: 82%
“…The isolation and characterization of lithium cyanocuprates 1a–c , which were prepared using amidolithium reagents with CuCN, revealed the bonding characteristics of Cu in systems that could demonstrate either higher or lower order structural properties. In line with theoretical expectations, 14 lower order (TMP) 2 Cu(CN)Li 2 (L) (L = OEt 2 , THF, THP = tetrahydropyran) 17 , 18 structures were observed crystallographically, with agglomeration giving essentially planar dimers based on lithium–nitrogen cores ( Scheme 1 ). The observation that, whilst in other respects 1a–c pertained to Lipshutz cuprate characteristics, they lack a Cu–CN interaction led to investigation of the generality of this motif.…”
Section: Introductionsupporting
confidence: 82%
“…The preparation of (TMP) 2 Cu(CN)Li 2 (THP) 8 served to extend the family of TMP-incorporating lithiocuprates based on the formulation (TMP) 2 Cu(CN)Li 2 (L) (L = OEt 2 1, THF 2) and to establish the prevalence of approximately flat dimers for these complexes in the solid state. 12,21 The use of thiocyanate instead of cyanide was then probed to investigate the former as a convenient, cheap and safe alternative that avoids redirecting reactivity in ways recently described when cyanide has been replaced by halide. 13 The resulting complexes showed interesting structural variability; the use of Et 2 O incurring an essentially planar dimer akin to those of 1, 2 and 8 but based on a (LiNCS) 2 core, while THF and TMP gave boat and chair conformers, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, and in line with the investigation of less expensive amide ligands, 51 the effect of replacing TMP with DMP has been studied by Harford et al 53 As noted above, attempts to fabricate Lipshutz-type cuprates analogous to 9, 10, 12 and 14-16 instead afforded the series of complexes 28, 29, 31 and 32 that have been interpreted as adducts between Lipshutztype and Gilman cuprates. The potential importance of this new structure-type is explained fully in the final section of this review where DFT analysis has suggested that the abstraction of LiX from Lipshutz or Lipshutz-type cuprates is fundamental to incurring in situ formation of the reactive base in DoC.…”
Section: New Amidocuprate Adducts and The Formation Of Reactive Speciesmentioning
confidence: 91%
“…52 The adoption of much cheaper amide ligands has gone handin-hand with the removal of some of the significant steric hindrance associated with TMP ligands, allowing fundamental changes to the orientation of the amide group and enabling the observation of new amidocuprate structure-types. 53 As noted above, the use of diethyl ether as a solvent enabled the synthesis and isolation of Lipshutz-type (TMP) 2 Cu-(Cl)Li 2 •OEt 2 14. However, upon exchanging the amide component for DMP a dramatic effect was observed.…”
Section: Amidocuprate Adducts: the Abstraction Of Lithium Halidementioning
confidence: 99%
See 1 more Smart Citation